Juegos motrices en el proceso de enseñanza aprendizaje para estudiantes del séptimo año de educación básica de la Escuela Carlos Coello Icaza del Cantón Vinces - Manjarrez Carriel, Henry José (2023)
The present work focused on motor games in the teaching-learning process for students of the seventh year of basic education of the Carlos Coello Icaza School of the Vinces canton", a topic that is of great relevance because motor development produces a series of changes that They help students express their feelings, relate to others and their environment, have self-control, flexibility, balance, and above all, develop basic motor skills. The methodology used for the development of this study was based on bibliographic and descriptive research. The methods used were inductive and analytical. The techniques that were used to obtain information regarding the subject under study were the interview, the survey and direct observation. The research instruments applied are: The interview questionnaire to know the opinion of the director and teacher of the seventh year of basic education of the educational institution under study. The survey questionnaire based on structured questions addressed to the students who contributed with relevant data for the development of this research. The direct observation sheet focused on the Evanm Test where neuromotor development was evaluated, obtaining results focused on aspects of body posture, balance, muscle tone, running and walking.